Thermodynamic and economic analysis of a supercritical carbon dioxide (S–CO2) recompression cycle with the radial-inflow turbine efficiency prediction. (15th January 2020) - Zhou, Aozheng; Li, Xue-song; Ren, Xiao-dong; Song, Jian; Gu, Chun-wei
Abstract: The turbine is one of the core components of the supercritical carbon dioxide (S–CO2 ) cycle system. Generally, a radial-inflow turbine is adopted for the small volume flow application. The turbine efficiency is closely related to the cycle parameters. In the previous studies about the S–CO2 cycle, the turbine efficiency is usually set as a constant value. In our previous studies of Organic Rankine Cycle (ORC), adopting a 1D model predicted turbine efficiency instead of a constant turbine efficiency is proved to have significant impacts on the system parameter determination. However, there was few researches about the influence of the turbine efficiency prediction method on the S–CO2 cycle design or optimization. In this paper, the analysis model of the S–CO2 recompression cycle with a one-dimensional (1D) radial-inflow turbine efficiency prediction model is presented, while others components off-design performance predicted models are not considered. The thermodynamic and economic performances of the S–CO2 cycle with the 1D model predicted turbine efficiency and constant turbine efficiency are analyzed and compared under different cycle design parameters and heat source conditions. The results indicate that for the S–CO2 cycle design and analysis, a proper constant turbine efficiency can be used when the heat source mass flow rate is constant. However, for some applications, the heat source mass flow rate is various according to the running time, especially for the low mass flow rate application, a 1D model predicted turbine efficiency should be used instead of a constant turbine efficiency. Highlights: The analysis model of the S–CO2 cycle with 1D turbine efficiency is presented. Analysis of the 1D turbine efficiency under different conditions is conducted. Performances with constant and 1D turbine efficiency are compared.